A Hazardous Chemical-Oriented Monitoring and Tracking System Based on Sensor Network. (21st May 2014) - Tan, Qiulin; Zhang, Yang; Zhang, Xiaofei; Pei, Xiangdong; Xiong, Jijun; Xue, Chenyang; Liu, Jun; Zhang, Wendong
We present a monitoring and tracking system for storage and transportation of chemicals. In accord with the standards and regulations of transport vehicles for hazardous chemicals, an overall structure-function diagram for vehicle monitoring and a pre-warning system were proposed by integrating various technologies such as computer modeling, control theory, multisensor data fusion, communication science, space positioning, and safety management science. Transportation experiments performed on sea and land demonstrated that the monitoring and tracking system is feasible with high precision, in which an amount of system state data was collected by different kinds of sensors group. Once sensor-derived signals were detected, the signals would be fused and transmitted to the master monitor center via a high precision and large-scale wireless communication network. The designed tracking and localizing system displayed good monitoring ability and adequately satisfied technical requirements.